Older persons and the law - Williams, John (Routledge, 2025)
"This book explores the law and legal system's impact on older persons. As well as describing the current law primarily in England and in Wales, it highlights the pivotal role that elder law lawyers play in using that law to challenge and combat ageism effectively. Important questions are raised about whether the law perpetuates ageism and whether the current working of the law effectively challenges discrimination, abuse, and social exclusion faced by older persons. Elder law lawyers have an essential role in advocating for the rights of older persons. The book focuses on the need to uphold and respect the human rights of older persons, emphasising their dignity, autonomy, and right to inclusion. It examines key topics such as human rights in the context of ageing, the provision of social care, discrimination, decision-making capacities, mental health, and abuse and neglect. It also offers insights into the notion of personal liberty concerning older persons and whether existing safeguards are sufficient. The international dimensions of elder law are discussed, highlighting the range of initiatives led by the United Nations and efforts by non-governmental organisations and regional bodies. These initiatives aim to confront and diminish ageism on both international and domestic fronts, emphasising the need for a concerted effort to enforce the rights of older persons across different cultures and legal systems. This book will interest researchers, students, and practitioners specialising in family and social welfare law, elder law, human rights law, and discrimination law"--